Um estudo sobre a relação entre Caio Prado Júnior e Fernando A. Novais - Mendes, Claudinei Magno Magre [UNESP] (Universidade Estadual de Maringa, 2013)
In this paper we propose to analyze the relationship established by Fernando Novais with Caio Prado regarding the studies about the colonization. Putting himself as his disciple, Novais exposes his conception of colonization as a deepening means and a way to overcome the way by which the author of Formação do Brasil contemporâneo understood the colonial phenomenon. This way of putting this relationship has been accepted by both the critics and supporters of Novais, thus acquiring certainty of truth. We show in this paper that by rooting his conception of colonization in Prado’s conception, Novais conceived him in a particular way: as an historian of the ‘sense of colonization’. The analysis of Prado’s concept of colonization shows, however, that this is part of his interpretation of the history of Brazil, as a whole. It follows that we can’t isolate one from the other without disturbing the comprehension of Prado’s conception. The result of our text is thus retaking the Prado’s conception in its historicity.

Em nosso texto, analisamos a relação entre Caio Prado e Fernando Novais no que diz respeito aos estudos acerca da colonização. Colocando-se como discípulo do primeiro, Novais expõe sua concepção de colonização como aprofundamento e superação do modo como o autor de Formação do Brasil contemporâneo entendia o fenômeno colonial. Essa maneira de colocar essa relação acabou sendo aceita tanto pelos partidários como pelos críticos de Novais, adquirindo foros de verdade. No entanto, para entroncar sua concepção de colonização na de Caio Prado, Novais concebeu-o de uma maneira particular, isto é, como um historiador do ‘sentido da colonização’. Um exame da concepção de colonização de Caio Prado mostra, todavia, que ela é parte integrante da sua interpretação da história do Brasil em seu conjunto. Resulta disso que não podemos isolar uma da outra, sem prejuízo para o entendimento da obra de Caio Prado. Retomar a obra de Caio Prado em sua historicidade constitui, pois, o resultado de nosso texto.
A study about the relation between Caio Prado Júnior and Fernando A. Novais
Keywords: Historiography; Colonization; Colonial economy; National economy; Historiografia; Colonização; Economia colonial; Economia nacional